Bouwfonds Kunstcollectie. - Bouwfonds Nederlandse Gemeenten, Hoevelaken (Hoevelaken : Bouwfonds Nederlandse Gemeenten, 1988)
Anzinger, Siegfried ; Armando ; Bakker, Sjoerd ; Birza, Rob ; Cremer, Jan ; van Elk, Ger ; de Groot, Arie ; Lucassen ; de Keyser, Raoul ; Rogge, Cornelius ; Visser, Carel ; Veneman, Peer ; van der Zee, Jan ; etc.
Nederlands
boek